Paradoks Akad Mudharabah Pada Simpanan Berjangka: Perspektif Anggota BMT X - Khoiroh, Fasta Bikul; Pudail, M.; Rifai, Fuad Yanuar Akhmad (AL-SULTHANIYAH, 2025)
Mudharabah contracts in Islamic finance ideally emphasize partnership, transparency, and risk sharing. However, practices in time deposits often deviate from these principles. This study reflects on customers’ understanding of mudharabah at a BMT in Magelang using a phenomenological qualitative approach through in-depth interviews with active customers and limited observation. Findings reveal that most customers perceive themselves as passive depositors expecting fixed returns, while the institution holds dominant authority in managing the funds and determining the profit-sharing ratio. This creates unequal power relations and practices resembling conventional deposits. The study concludes a paradox between sharia ideals and practice, highlighting the need for financial literacy, transparency, and customer involvement to realize true partnership.